Preparation of Population Data Base for Community Unit 11 East Pamulang Village, Pamulang District South Tangerang City - Edi Rusdiyanto; Siti Umamah Naili Muna; Sumartono Sumartono; Abdillah Munawir (LPPM UIKA Bogor, 2023)
Village and sub-district administration, neighborhood unit functions to record population data and other government administration services, maintain security, support, and inter-living harmony, generate ideas in the implementation of development by developing the aspirations and genuine self-help of the community, and activating self-help cooperation and participation of the community members in their area. So that the purpose of implementing AbdiMas is to increase understanding of simple technology in processing population databases in neighborhood units and Community Unit 11 East Pamulang Village administrators. The method used is Active and Participatory Learning with material discussions, practices, and demonstrations. The results of the training and database input based on all available information provide a very simple understanding of technological knowledge using Microsoft Office Excel and add broad insight to local neighborhood units and Community Unit 11 administrators on the importance of inputting databases to facilitate all the interests and aspirations of the community for the implementation of village government as well as the village. Overall, 90% of the neighborhood and Community Unit 11 administrators understand the use and input of databases using Microsoft Excel, making it easier to formulate policies related to education, health, economy, and social affairs, the government of East Pamulang Village, South Tangerang City.